Transfusion management in a pediatric patient with febrile neutropenia with red blood cell autoantibodies: a case report - Jain, Ashish; Ramakrishnan, Sharanya; Tripathi, Parmatma Prasad; Hans, Rekha; Bansal, Deepak; Sharma, Ratti Ram (International Journal of Research in Medical Sciences, 2021)
Febrile neutropenia is a common complication of chemotherapy especially in hematological malignancies associated with sepsis or severe infection. We report a case where a seven-year-old girl with T – cell acute lymphoblastic leukemia (ALL) developed febrile neutropenia (absolute neutrophil count - ANC <500/µL). Patient developed transient red blood cell (RBC) autoantibodies which interfered with compatibility testing and posed a challenge in donor selection for granulocyte transfusion. Direct antiglobulin test (DAT) and compatibility testing were done by column agglutination technique (CAT) using polyspecific anti-human globulin gel cards. Antibody screen was also done by CAT using 3-cell panel. Granulocyte concentrate was collected from eligible donors after taking an informed consent using a cell separator based on continuous flow principle. The patient’s blood group was AB RhD positive, however, the auto-control was positive (2+), DAT was positive (1+) but the antibody screen was negative. Monospecific DAT revealed the characteristic of antibody to be IgG (2+). The donor for granulocyte harvesting was selected on the basis of adopting a least incompatible donor approach. During her hospital stay she was transfused with four granulocyte concentrates, and other blood components without any adverse events. The patient’s blood culture was sterile on day 33 of hospital stay and subsequently she remained afebrile and finally discharged on day 41 in a hemodynamically stable state. The hemogram was- Hb:10.7g/dL, Total leucocyte count (TLC): 5610/µL, ANC: 4375/µL, PLT: 22000 /µL. This case draws a special attention to the importance of serological testing in selection of donor for granulocyte transfusion.